Siege - Correia, Larry (Riverdale, NY Baen, 2017)
"When Monster Hunter International's top hunter, Owen Zastava Pitt, was given a tip about some missing hunters, he didn't realize their rescue mission would snowball into the single biggest operation in MHI's history. Their men are being held prisoner in a nightmare dimension only reachable through radioactive ruins of a monster-infested war zone. And it is also the home base of the powerful creature behind the devastating attacks on the Last Dragon and Copper Lake. It turns out ancient gods of chaos really hate trespassers. So now it is D-Day at the City of Monsters"--
113824
Keywords: Monsters -- Fiction; Hunters -- Fiction; Fiction -- Fantasy -- Contemporary; Fiction -- Fantasy -- Urban Life; Fantasy fiction; Fiction